Tongue Lesions Diagnostic Challenges and Therapeutic Strategies - Sakr, Mahmoud F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book offers in a single resource the whole coverage of different diseases and lesions, congenital or acquired, of the tongue, along with a complete spectrum of surgical techniques that can be used to achieve the best functional and aesthetic results. In addition to tongue embryology, surgical anatomy, histology and physiology, the book explores the differential diagnosis of congenital anomalies of the tongue and lingual lesions, as well as the most recent advances in surgical management (resection, reconstruction and surgical management of the neck in patients with tongue cancer). The volume includes unique chapters about tongue replantation and tongue allo-transplantation. Richly illustrated, this book provides an indispensable source of knowledge to all specialists and trainees entrusted with the care of patients suffering from tongue lesions.
Preface. Embryology of the Tongue. - Surgical Anatomy of the Tongue -- Histology of the Tongue -- Physiology of the Tongue -- Congenital Anomalies -- Tongue Trauma -- Tongue Piercing -- Tongue Discoloration -- Inflammation (Glossitis) -- Tongue Fissures -- Swellings of the Tongue -- Tumors of the tongue -- Ulcers of the Tongue -- Glossectomy -- Reconstruction after Glossectomy -- Surgical Management of the Neck -- Tongue Replantation -- Tongue Transplantation. .
Keywords: Otorhinolaryngology; Oncology; Mouth -- Surgery; Surgery, Plastic; Otorhinolaryngology; Oncology; Oral and Maxillofacial Surgery; Plastic Surgery; Tongue Diseases--diagnosis